2005
DOI: 10.1111/j.0105-1873.2005.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the localization of foot dermatitis and the causative allergens in shoes: a 13‐year retrospective study

Abstract: The purpose of this retrospective study was to test whether the initial pattern of clinical presentation of shoe dermatitis could indicate the causative allergen(s) and to estimate the odds on foot dermatitis in patients with a positive patch test versus those with a negative patch-test result. Between 1990 and 2002, 8543 patients were patch tested with the standard series (and additional allergens, if appropriate). Of them, 1168 (14%) had been referred because of foot dermatitis and 474 of these patients (5.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
67
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 26 publications
13
67
3
1
Order By: Relevance
“…31 In this study of NACDG patients, only hexavalent potassium dichromate was tested and was found to be the second most frequent shoe-related allergen, accounting for 17.5% of positive reactions. European, 7,8,13,17 Mediterranean, 18 and Indian 2,21 studies of patients with foot dermatitis found potassium dichromate to be the most frequent allergen, accounting for 10.0 to 43.0% of relevant positive reactions. When the data from published studies were pooled, potassium dichromate was the most frequent individual allergen, accounting for 31.5% of reactions.…”
Section: Potassium Dichromatementioning
confidence: 99%
See 2 more Smart Citations
“…31 In this study of NACDG patients, only hexavalent potassium dichromate was tested and was found to be the second most frequent shoe-related allergen, accounting for 17.5% of positive reactions. European, 7,8,13,17 Mediterranean, 18 and Indian 2,21 studies of patients with foot dermatitis found potassium dichromate to be the most frequent allergen, accounting for 10.0 to 43.0% of relevant positive reactions. When the data from published studies were pooled, potassium dichromate was the most frequent individual allergen, accounting for 31.5% of reactions.…”
Section: Potassium Dichromatementioning
confidence: 99%
“…5,6 The most common allergens associated with ACD of the feet vary among studies but are typically those involved in leather or rubber processing. 1,[7][8][9][10] The warm moist environment and occlusion provided by shoes are thought to potentiate the development of ACD. 11 ACD from shoes can be debilitating, and the causative agent may not be obvious.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is often included in patch testing series and is a recognized foot dermatitis allergen. 25 Nardelli et al 25 reported 11 positive patch test results to benzoyl peroxide in their 13-year retrospective study in Belgium. In addition, Vidovi( et al 26 discussed the case of workers in a factory producing shoes from polyvinyl chloride who became sensitized to dibutylphthalate, a plasticizer.…”
mentioning
confidence: 99%
“…chungen wurde über positive Reaktionen auf 0,25% p-Aminoazobenzol bei Patienten mit Fußdermatitis berichtet (Nardelli et al 2005;Saha et al 1993). Zwischen 1980 und 1993 reagierten von 379 Friseuren 174 positiv auf 1% p-Phenylendiamin und 121 positiv auf 0,25% p-Aminoazobenzol (Conde-Salazar et al 1995).…”
unclassified